(untitled) (Plant Tissue Culture and Biotechnology, 2009)
Effects of different concentrations of 2-ip and IBA in WPM basal medium for Blomidon blueberry in vitro propagation and four different rooting agents at the early stage after transplantation showed that 15 mg/l of 2-ip is the best concentration to induce shoots. For optimum in vitro root formation 10 µM IBA was found to be best and four rooting agents for seedling transplantation according to their effects were No.2>, No.4>, No.3 >, water > and No. 1. Key words: Blomidon, Tissue culture, In vitro regeneration, Rooting agent D.O.I. 10.3329/ptcb.v18i2.3650 Plant Tissue Cult. & Biotech. 18(1): 187-195, 2008 (December)